Placentitis Bacterial as a cause of abortion in mares: Case Report (Orinoquia, 2018)
Placentitis in mares caused by bacteria is one of the most important causes of abortions, there aren’t any documented cases in Colombia as of yet. In this article, we take a look at a particular case of a “Silla Francesa” mare 10 years of age. The Mare had an abortion at 9 months of gestation and was treated at the Veterinary Clinic San Jorge - Army Equitation School from Bogota. The mare suffered from a premature lactation and presented thickening in the placenta which indicaented placentitis, showing signs of vascular changes (congestion, edema and fibrin).In gram staining of placenta, It was found a negative gram coccobacilli adhered to the surface of the chorioallantoic villus cells and mixed with the proteinaceous material, apparently some are located intracellularly, confirming the process of infection potentially due to the presence of enterobacteias. (E.coli or Salmonella sp).
Keywords: Abortion; enterobacteria; fetus; placenta; mare